State Administrative Court in Providing Legal Protection Against Administrative Decisions That Are Harmful to Citizens - Ronald Christyanto Soegiarto; Nur Achmad Rifai Ridwan; Priangga Charis Pratama (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
The State Administrative Court (PTUN) was established as a legal protection instrument in Indonesia's rule of law to correct administrative actions of officials that harm citizens. However, in practice, the PTUN has not been fully able to fulfill its ideal function as a bastion of justice. This study examines the gap between das sollen and das sein in the performance of the PTUN, particularly regarding the implementation of decisions that have become final. Legal uncertainty arises from the continued granting of judicial review (PK) authority to TUN officials who lose their cases, weak execution mechanisms, and the absence of a supervisory body for the implementation of decisions. Furthermore, the legal culture of officials that does not respect the finality of decisions also contributes to sociological obstacles. This study uses normative and sociological approaches to identify regulatory, institutional, and legal culture constraints, while also formulating necessary reform measures. Through empirical case analysis, such as the Jayapura Administrative Court decision No. 6/G/LH/2023/PTUN.JPR regarding the customary land dispute of the Awyu tribe, the study formulated several urgent reform measures. With these steps, the Administrative Court can function more effectively as a tangible form of administrative legal protection, while strengthening the legitimacy of the judiciary and public confidence in the rule of law in Indonesia.